Jovens em cena: a formação humana através da autonomia e do protagonismo juvenil - Conrad, Vanderleia Lucia Dick (2019)
This critical reflective report aims to understand how pedagogical practices developed in the Sociedade Esportiva e Literária – SEL (Sports and Literature Society) at Colégio Militar de Porto Alegre (a Military School in Porto Alegre, Brazil) promote their protagonism and autonomy. Considering the immersion in a culture of military education, this research has sought to investigate whether such practices contribute to a humanized whole education for these adolescents. A qualitative methodology has been adopted through action-research. The concepts of authonomy and protagonism emphasized in this project are strictly related to the idea of providing proper environment and conditions for the youth to get involved in activities which include real-world problem solving, besides demanding from them qualities such as initiative, time management, and commitment. The results from the data analysis and based in the teen protagonism scale porposed by Costa have shown the gradual process related to their protagonism and pedagogical practices developed to the students from SEL through the concrete experiences have contributed meaningfully to their autonomy development.